Lablab (Lablab purpureus L.) genotypes and field margin vegetation influence bean aphids and their natural enemies - Karimi, Joseph M.; Nyaanga, Jane G.; Mulwa, Richard M.S.; Ogendo, Joshua O.; Bett, Philip K.; Cheruiyot, Erick K.; Arnold, Sarah E.J.; Belmain, Steven R.; Stevenson, Philip C. (Frontiers in Insect Science, 2024)
Dolichos bean (Lablab purpureus L.) is an important food and livestock feed legume that can also enhance soil fertility. However, its production is limited by insect pests, notably the black bean aphid (Aphis fabae). The present field study was conducted to determine the difference in contribution of dolichos genotypes and natural field margin vegetation (FMV) on the abundance and diversity of natural enemies and the damage, incidence and abundance of bean aphids. Eighteen lablab genotypes were planted in the presence or absence of FMV in a randomized complete block design experiment replicated four times. Data on aphid abundance, incidence and severity of damage were collected at four growth stages of the crop. Dolichos genotypes significantly influenced aphid incidence thereby suggesting some level of tolerance to aphid colonization. Findings showed that dolichos genotypes were significant for natural enemies species richness with no statistical difference for abundance and natural enemies species diversity. However, the genotypes did not vary significantly in their influence on numbers of aphid natural enemies. FMV was associated with low bean aphid damage. Overall, the presence or absence of FMV did not influence the number of natural enemies caught on the crop. This concurs with recent work that shows similar numbers of natural enemies with field margin plants but may reflect the reduced number of pest insects. Cropping seasons influenced aphid abundance and damage severity, with the populations developing at early stages of lablab development and decreasing as the crop advanced. This pattern was similar both in presence or absence of FMV. The findings of this study highlight the important contribution of crop genotype together with the presence of field margin species in the regulation of aphids and their natural enemies in lablab.